Regulatory Policy Content of Hazardous Materials Mercury in Illegal Bleaching Creams - Syafrijon Syafrijon; Syahfori Widiyani; Aldri Frinaldi; Rembrandt Rembrandt; Dasman Lanin; Genius Umar (Science and Environmental Journal for Postgraduate, 2023)
Mercury (Hg) is a metal element that is often used in technology development, especially in the beauty sector. Several brands of creams can be seen in the market, have no manufacturing or expiry date stated, labeling is incomplete, or contain levels of bleach which can only harm the skin itself. The creams may have up to 10,000 ingredients in them, common ones being steroids, arbutin, ascorbic acid, hydroquinone, and kojic acid, including high levels of toxic metals such as mercury. There are still many Indonesian women who lose that white and smooth skin is a symbol of beauty. This makes them do various ways to get white and smooth skin. Facial whitening creams that contain mercury metal in cosmetic ingredients are widely used. Cosmetic products containing mercury generally promise a white face in a short time, so many women are interested in using them. This is used by cosmetic manufacturers who sell face whitening creams containing hazardous ingredients, such as mercury. Public policies need to be regulated to prevent impacts on the skin health of users. This article is the result of a study from several sources, namely information that appears in the community and also through several articles.